AvrE1 and HopR1 from Pseudomonas syringae pv. actinidiae are additively required for full virulence on kiwifruit. (23rd September 2020) - Jayaraman, Jay; Yoon, Minsoo; Applegate, Emma R.; Stroud, Erin A.; Templeton, Matthew D.
Abstract: Pseudomonas syringae pv. actinidiae ICMP 18884 biovar 3 (Psa3) produces necrotic lesions during infection of its kiwifruit host. Bacterial growth in planta and lesion formation are dependent upon a functional type III secretion system (T3S), which translocates multiple effector proteins into host cells. Associated with the T3S locus is the conserved effector locus (CEL), which has been characterized and shown to be essential for the full virulence in other P. syringae pathovars. Two effectors at the CEL, hopM1 and avrE1, as well as an avrE1 ‐related non‐CEL effector, hopR1, have been shown to be redundant in the model pathogen P. syringae pv. tomato DC3000 (Pto), a close relative of Psa. However, it is not known whether CEL‐related effectors are required for Psa pathogenicity. The Psa3 allele of hopM1, and its associated chaperone, shcM, have diverged significantly from their orthologs in Pto. Furthermore, the CEL effector hopAA1‐1, as well as a related non‐CEL effector, hopAA1‐2, have both been pseudogenized. We have shown that HopM1 does not contribute to Psa3 virulence due to a truncation in shcM, a truncation conserved in the Psa lineage, probably due to the need to evade HopM1‐triggered immunity in kiwifruit. We characterized the virulence contribution of CEL and related effectors in Psa3 and found that only avrE1 and hopR1, additively, are required for in planta growth and lesion production. This is unlike the redundancy described for these effectors in Pto and indicates that these two Psa3 genes are key determinants essential for kiwifruit bacterial canker disease. Abstract : The virulence contribution of CEL‐encoded effector AvrE1 and its phylogenetically related non‐CEL effector HopR1 from Psa3 are nonredundantly required for in planta Psa growth and lesion production on susceptible kiwifruit hosts.